Yeast AP-1 like transcription factors (Yap) and stress response: a current overview - Rodrigues-Pousada, Claudina (Microb Cell, 2019)
Yeast adaptation to stress has been extensively studied. It involves large reprogramming of genome expression operated by many, more or less specific, transcription factors. Here, we review our current knowledge on the function of the eight Yap transcription factors (Yap1 to Yap8) in Saccharomyces cerevisiae, which were shown to be involved in various stress responses. More precisely, Yap1 is activated under oxidative stress, Yap2/Cad1 under cadmium, Yap4/Cin5 and Yap6 under osmotic shock, Yap5 under iron overload and Yap8/Arr1 by arsenic compounds. Yap3 and Yap7 seem to be involved in hydroquinone and nitrosative stresses, respectively. The data presented in this article illustrate how much knowledge on the function of these Yap transcription factors is advanced. The evolution of the Yap family and its roles in various pathogenic and non-pathogenic fungal species is discussed in the last section.